Determination of the Side-Reaction Coefficient of Desferrioxamine B in Trace-Metal-Free Seawater - Schijf, Johan; Burns, Shannon M. (Frontiers in Marine Science, 2016)
Electrochemical techniques like adsorptive cathodic stripping voltammetry with competitive ligand equilibration (ACSV-CLE) can determine total concentrations of marine organic ligands and their conditional binding constants for specific metals, but cannot identify them. Individual organic ligands, isolated from microbial cultures or biosynthesized through genomics, can be structurally characterized via NMR and tandem MS analysis, but this is tedious and time-consuming. A complementary approach is to compare known properties of natural ligands, particularly their conditional binding constants, with those of model organic ligands, measured under suitable conditions. Such comparisons cannot be meaningfully interpreted unless the side-reaction coefficient (SRC) of the model ligand in seawater is thoroughly evaluated. We conducted series of potentiometric titrations, in non-coordinating medium at seawater ionic strength (0.7 M NaClO4) over a range of metal:ligand molar ratios, to study complexation of the siderophore desferrioxamine B (DFOB) with Mg and Ca, for which it has the highest affinity among the major seasalt cations. From similar titrations of acetohydroxamic acid in the absence and presence of methanesulfonate (mesylate), it was determined that Mg and Ca binding to this common DFOB counter-ion is not strong enough to interfere with the DFOB titrations. Stability constants were measured for all DFOB complexes with Mg and Ca including, for the first time, the bidentate complexes. No evidence was found for Mg and Ca coordination with the DFOB terminal amine. From the improved DFOB speciation, we calculated five SRCs for each of the five (de)protonated forms of DFOB in trace-metal-free seawater, yet we also present a more convenient definition of a single SRC that allows adjustment of all DFOB stability constants to seawater conditions, no matter which of these forms is selected as the 'component' (reference species). An example of Cd speciation in seawater containing DFOB illustrates the non-trivial use of different SRCs for polyprotic, polydentate organic ligands.